2015
DOI: 10.1016/j.scr.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a candidate stem cell in human gallbladder

Abstract: There are currently no reports of the identification of stem cells in the human gallbladder. The differences between human gallbladder and intrahepatic bile duct (IHBD) cells have also not been explored. The goals of this study were to evaluate if human fetal gallbladder contains a candidate stem cell population and if fetal gallbladder cells are distinct from fetal IHBD cells. We found that EpCAM+CD44+CD13+ cells represent the cell population most enriched for clonal self-renewal from primary gallbladder. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…The cell surface markers, CD26, CD29, CD44, CD54, CD49b, CD49f CD133, CD90 and CD326 (EpCam) have been reported to be present on human SC and CSC in various solid tumors [44-51]. CD24 and CD66 have been shown to identify mature/differentiated cells in normal and cancer tissues, including breast cancer [52, 53]. CD49c, CD81, CD104 and EGFR have been considered to be cancer or epithelial cancer cell markers [54-57].…”
Section: Resultsmentioning
confidence: 99%
“…The cell surface markers, CD26, CD29, CD44, CD54, CD49b, CD49f CD133, CD90 and CD326 (EpCam) have been reported to be present on human SC and CSC in various solid tumors [44-51]. CD24 and CD66 have been shown to identify mature/differentiated cells in normal and cancer tissues, including breast cancer [52, 53]. CD49c, CD81, CD104 and EGFR have been considered to be cancer or epithelial cancer cell markers [54-57].…”
Section: Resultsmentioning
confidence: 99%
“…The cells tend to moderately produce mucins ( 35 ) and transport bile and organic ions ( 36 38 ). They share many similarities with the cholangiocytes of the intrahepatic bile duct ( 39 ), and therefore the stem cells of the adult gallbladder might express similar markers, such as CD44, CD13, and LGR5 ( 40 , 41 ) and also depend on activation of the Wnt/β-catenin pathway for their maintenance ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results from KEGG analysis demonstrated that the 10 hub genes were enriched in the following pathways: ‘TGF-β signaling pathway’, ‘signaling pathways regulating pluripotency of stem cells’ and ‘complement and coagulation cascades’. These pathways have been associated with the development and progression of gallbladder cancer ( 42 44 ). For example, the crosstalk between the TGF-β signaling pathway and lncRNAs plays a key role in cancer.…”
Section: Discussionmentioning
confidence: 99%